Improving Patient Experience of Care Providers in a Multispecialty Ambulatory Pediatrics Practice. (January 2019) - Fustino, Nicholas J.; Moore, Paige; Viers, Sandy; Cheyne, Ken
Patient experience is positively associated with superior medical outcomes, clinical quality, patient safety measures, physician job satisfaction, doctor-patient communication, and patient compliance with treatment recommendations. A concrete pediatrics-focused methodology for improving patient experience in a multispecialty ambulatory setting has not been described, nor has the impact on practice outcomes been assessed. The primary aim of this study was to improve patient experience care provider scores at a single multiclinic children's hospital in the Midwest to the 70th percentile in a 5-year period. The secondary aim sought to determine the impact of quality improvement efforts on practice growth, patient complaint rate, and provider/staff engagement. Patient experience was measured by returned Press-Ganey surveys. Interventions involved establishing infrastructure, promoting feedback and transparency, providing education, and transforming culture. Provider scores improved from the 19th to the 70th percentile within 5 years. Practice volume increased by 17.1%; patient complaint/grievance frequency decreased 33-fold; and provider/staff engagement did not appreciably change.